Corneal confocal microscopy differentiates inflammatory from diabetic neuropathy - Fleischer, Michael; Lee, Inn; Erdlenbruch, Friedrich; Hinrichs, Lena; Petropoulos, Ioannis N; Malik, Rayaz A; Hartung, Hans-Peter; Kieseier, Bernd C; Kleinschnitz, Christoph; Stettner, Mark (Journal of neuroinflammation, 2021)
BACKGROUND: Immune-mediated neuropathies, such as chronic inflammatory demyelinating polyneuropathy (CIDP) are treatable neuropathies. Among individuals with diabetic neuropathy, it remains a challenge to identify those individuals who develop CIDP. Corneal confocal microscopy (CCM) has been shown to detect corneal nerve fiber loss and cellular infiltrates in the sub-basal layer of the cornea. The objective of the study was to determine whether CCM can distinguish diabetic neuropathy from CIDP and whether CCM can detect CIDP in persons with coexisting diabetes. METHODS: In this multicenter, case-control study, participants with CIDP (n = 55) with (n = 10) and without (n = 45) diabetes; participants with diabetes (n = 58) with (n = 28) and without (n = 30) diabetic neuropathy, and healthy controls (n = 58) underwent CCM. Corneal nerve fiber density (CNFD), corneal nerve fiber length (CNFL), corneal nerve branch density (CNBD), and dendritic and non-dendritic cell density, with or without nerve fiber contact were quantified. RESULTS: Dendritic cell density in proximity to corneal nerve fibers was significantly higher in participants with CIDP with and without diabetes compared to participants with diabetic neuropathy and controls. CNFD, CNFL, and CNBD were equally reduced in participants with CIDP, diabetic neuropathy, and CIDP with diabetes. CONCLUSIONS: An increase in dendritic cell density identifies persons with CIDP. CCM may, therefore, be useful to differentiate inflammatory from non-inflammatory diabetic neuropathy.
Keywords: dospělí; diferenciální diagnóza; Female; Diabetic Neuropathies; Adult; ženské pohlaví; rohovka; Dendrites; Diabetes Mellitus, Type 2; Cornea; dendrity; lidé; chronická zánětlivá demyelinizační polyneuropatie; Diabetes mellitus; diabetes mellitus 2. typu; studie případů a kontrol; Diagnosis, Differential; Male; Case-Control Studies; Aged; lidé středního věku; Nerve Fibers; nervová vlákna; senioři; mužské pohlaví; Microscopy, Confocal; konfokální mikroskopie; Polyradiculoneuropathy, Chronic Inflammatory Demyelinating; diabetické neuropatie; corneal confocal microscopy; Middle Aged; Chronic inflammatory demyelinating neuropathy; Humans